Kemampuan Membaca Pemahaman Siswa Sekolah Dasar [Reading Comprehension Skills of Elementary School Students] - Sarah Adelheit Frans; Yubali Ani; Yesaya Adhi Wijaya (Universitas Pelita Harapan, 2023)
The ability to read comprehensively is the key to success in education. The ability to read comprehensively can help students understand in depth the contents of a reading so that students' knowledge can develop. This ability has been taught since the third grade of elementary school and its development is specifically carried out in Indonesian Language lessons but is useful in other subjects. However, there are still problems with low reading comprehension skills at the elementary level to a higher level. The purpose of writing this paper is to present the reading comprehension ability of elementary school students. The method of writing is a literature review by conducting an assessment of various sources. The results of the study show that the low reading comprehension ability is caused by low interest in reading, lack of motivation, until learning to read comprehension is boring. The teacher's role is needed in selecting and implementing appropriate reading comprehension learning strategies to be able to improve these abilities. There are many types of reading comprehension learning strategies and teachers must choose and apply the right strategies so that students can achieve learning objectives. The teacher's role in selecting and implementing learning strategies is influenced by the value system held by the teacher. Christian teachers must see their students as Imago Dei with their own uniqueness and diverse needs. In this way, Christian teachers will help students grow holistically. BAHASA INDONESIA ABSTRACT: Kemampuan membaca secara komprehensif merupakan kunci keberhasilan dalam dunia pendidikan.Kemampuan membaca komprehensif dapat membantu siswa memahami secara mendalam isi suatu bacaan sehingga pengetahuan siswa dapat berkembang.Kemampuan ini telah diajarkan sejak kelas tiga sekolah dasar dan pengembangannya secara khusus dilakukan pada pelajaran Bahasa Indonesia, namun bermanfaat pada mata pelajaran lainnya.Namun, masih terdapat permasalahan rendahnya kemampuan membaca pemahaman di tingkat sekolah dasar hingga ke jenjang yang lebih tinggi.Tujuan penulisan makalah ini adalah untuk memaparkan kemampuan membaca pemahaman siswa sekolah dasar.Metode penulisan yang digunakan adalah kajian literatur dengan melakukan pengkajian dari berbagai sumber.Hasil kajian menunjukkan bahwa rendahnya kemampuan membaca pemahaman disebabkan oleh rendahnya minat baca, kurangnya motivasi, hingga pembelajaran membaca pemahaman yang membosankan.Peran guru sangat dibutuhkan dalam memilih dan menerapkan strategi pembelajaran membaca pemahaman yang tepat untuk dapat meningkatkan kemampuan tersebut.Ada banyak jenis strategi pembelajaran membaca pemahaman dan guru harus memilih dan menerapkan strategi yang tepat agar siswa dapat mencapai tujuan pembelajaran.Peran guru dalam memilih dan menerapkan strategi pembelajaran dipengaruhi oleh sistem nilai yang dianut oleh guru.Guru Kristen harus melihat murid-muridnya sebagai Imago Dei dengan keunikan dan kebutuhan yang beragam. Dengan cara ini, guru-guru Kristen akan membantu para siswa bertumbuh secara holistik.